Case report: VEXAS syndrome: an atypical indolent presentation as sacroiliitis with molecular response to azacitidine - Pereira da Costa, Roberto; Sapinho, Guilherme; Bandeira, Matilde; Infante, Joana; Marques, Tiago; Mimoso Santos, Carla; Forjaz de Lacerda, João; Fonseca, João Eurico; Romeu, José Carlos (Frontiers in Immunology, 2024)
VEXAS syndrome is a recently described autoinflammatory syndrome caused by somatic acquisition of UBA1 mutations in myeloid precursors and is frequently associated with hematologic malignancies, chiefly myelodysplastic syndromes. Disease presentation can mimic several rheumatologic disorders, delaying the diagnosis. We describe a case of atypical presentation resembling a late-onset axial spondylarthritis, later progressing to a systemic inflammatory syndrome with chondritis, cutaneous vasculitis and transfusion-dependent anemia, requiring high doses of steroids. Ruxolitinib was used as a first steroid-sparing strategy without response. However, azacitidine showed activity in controlling both inflammation and the mutant clone. This case raises the question of whether azacitidine's antiinflammatory effects are dependent or independent from clonal control. We discuss the potential relevance of molecular remission in VEXAS syndrome and highlight the importance of a multidisciplinary team for the care of such complex patients.